Effect of Cooking on Lignans Content in Whole‐Grain Pasta Made with Different Cereals and Other Seeds. Issue 2 (1st March 2013) - Durazzo, Alessandra; Azzini, Elena; Turfani, Valeria; Polito, Angela; Maiani, Giuseppe; Carcea, Marina
ABSTRACT: Lignans are of increasing interest because of their potential anticarcinogenic, antioxidant, estrogenic, and antiestrogenic activities. In this work, mixed‐cereal pastas manufactured by adding 60% whole‐grain flours of different cereals (wheat, oat, rye, barley, and rice) to durum wheat semolina, a multigrain pasta with different grains (cereals, legumes, and flaxseed), and a traditional industrial durum wheat semolina were analyzed for their lignans content both in the raw and in the cooked state, ready for consumption. For raw mixed‐cereal pastas, total lignans were within the range 94.91–485.62 μg/100 g d.w. After cooking, total lignans losses of about 35.5, 18.31, and 5.46% were observed respectively in oat‐, rye‐, and rice‐added pastas, whereas increases of 5.74 and 13.62% were observed in barley‐added and whole durum wheat pastas. Interesting results were obtained for the multigrain pasta: the raw product exhibited a total lignans content of 9, 686.17 ± 287.03 μg/100 g d.w., and the major contribution was given by secoisolariciresinol. This highest total lignans value resulted from its rich and varied composition in seeds of different origin, legumes, and flaxseed in particular. Our findings showed that mixed‐cereal and multigrain pastas can be considered a good source of lignans. The effect of cooking was not the same for each product, and it depended on the different lignans profile of each grain, on the different chemical structure of each lignan, and on the nature of the food matrix.